Attitude & Practices of Hospital Staff Towards Safety In A Tertiary Care Hospital, Pune – A Compilation of Safety Experiments - Kurapatti Ambika Shrinivas1 , Neha Ahire2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction -Safety is a critical component to the quality health care. The culture of safety extends topatients, staff, caregivers, and attendants and to anyone visiting the hospital. As health care organizationsendeavor to improve their quality of care, there is growing recognition of the importance of establishing aculture of safety. With growing awareness of accreditations like NABH and JCI, the focus on safety cultureis rising. Safety culture plays a vital role and it comes with hospital team effort, at protecting patients andstaff from harm and empowered to do the right thing. The study observes attitudes and practices towardssafety culture.Aim & Objectives – The study aims to conduct various safety experiments to assess the attitudes and observethe practices towards the safety culture. The study also identifies areas for potential safety improvements.Methodology – The study was an observational one where the response of the staff of the hospital was notedtowards a particular pre-planned event leading to breach of safety or deviation from the safety norms. Theresponse of the staff members who have witnessed deviations were noted.Results & Conclusion - The results showed that most of the hospital staff of this hospital feel positivelytoward patient safety culture in their organization. The training needs and areas of improvement wereidentified.. Such safety experiments should be conducted from time to time to know error and event reporting